A coarse aggregate ultra-high performance concrete and preparation method thereof

By modifying graphene oxide as a dispersant of silica fume, the problem of difficulty in dispersing silica fume in concrete is solved, the later strength and durability of concrete are improved, and the surface damage and loss of seepage resistance caused by steam curing are avoided.

CN118702453BActive Publication Date: 2025-02-11THE FIRST ENGINEERING COMPANY OF CCCC FOURTH HARBOUR ENGINEERING CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411058877.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-02
Publication Date
2025-02-11
Estimated Expiration
2044-08-02

AI Technical Summary

Technical Problem

Due to its small particle size and large specific surface area, silica fume is difficult to disperse effectively, resulting in the infilling and synergistic hydration effect being unable to fully exert. At the same time, steam curing can easily lead to damage to the concrete surface and reduced permeability.

Method used

Modified graphene oxide is used as the dispersant of silica fume. By modifying the surface of graphene oxide, the positive charge is increased so as to adsorb the negative charge silicon fume, prevent the accumulation of graphene oxide sheet structure, and the surface of silica fume The hydroxyl group reaction reduces its surface energy and achieves effective dispersion of silicon fume.

Benefits of technology

It effectively improves the later strength and durability of concrete, avoids the problems of concrete surface damage and reduced permeability caused by fume agglomeration and steam curing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118702453B_ABST
    Figure CN118702453B_ABST
Patent Text Reader

Abstract

The invention discloses a coarse aggregate ultra-high performance concrete and a preparation method thereof, belonging to the technical field of concrete. The coarse aggregate ultra-high performance concrete of the invention comprises, in terms of mix ratio, 600-800 kg / m of cement as raw materials. 3 , silica fume 150~300kg / m 3 , fly ash 100~150kg / m 3 , Sand 600~750kg / m 3 , Crushed stone 350~600kg / m 3 , admixture 100~200kg / m 3 , Steel fiber 150~250kg / m 3 , water reducing agent 8~25kg / m 3 , Water 100~180kg / m 3 , silica fume dispersant 0.5~1kg / m 3 , the silica fume dispersant is modified graphene oxide, specifically at least one of amino graphene oxide and quaternary ammonium graphene oxide. The silica fume dispersant in the present invention is prepared based on modified graphene oxide, and the obtained silica fume dispersant can effectively disperse silica fume, and through the synergistic effect of the silica fume dispersant combined with silica fume, the proportion of macropores in concrete is reduced and the proportion of small pores is increased, effectively improving the strength and durability of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete, and in particular to a coarse aggregate ultra-high performance concrete and a preparation method thereof. Background Art

[0002] Ultra-high performance concrete has the advantages of high strength, high corrosion resistance and durability, and can reduce structure size, reduce structure deadweight, save land, reduce energy consumption, and reduce structure maintenance and reconstruction costs.

[0003] Silica fume is a kind of mineral admixture that is collected by special devices from the dust overflowed with exhaust gas during the smelting of ferrosilicon ore. The output of silica fume is relatively large. If it cannot be used in time, it will have a huge impact on the environment. Adding silica fume to concrete has become a common phenomenon in concrete production in recent years. The addition of silica fume provides a new solution for the utilization of silica fume, and at the same time, the addition of silica fume improves the performance of concrete. However, in actual application, silica fume has the following obvious problems due to its actual production application: silica fume is one of the mineral admixtures with the lowest density, and the powder is loose and easy to fly, which makes it difficult to transport, store and use; due to the small particle size and large specific surface area of ​​silica fume, it is easy to agglomerate, and its surface electronegativity is large, so it is difficult to effectively disperse it by conventional physical and mechanical dispersion methods, resulting in the filling effect and synergistic hydration effect of silica fume cannot be fully exerted. Densified silica fume can effectively solve the problems of transportation and storage. The use of densified silica fume inevitably requires the addition of dispersants, but the addition of too much dispersant often affects the early strength of concrete. Steam curing is a curing method often used in low-temperature production environments. Its main function is to improve the early strength of concrete. However, one of the negative effects of steam curing is that it can easily cause the pores inside the concrete to move toward the surface, and the pore diameter becomes larger, resulting in concrete surface damage, reduced impermeability and other quality deterioration consequences. Summary of the invention

[0004] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a coarse aggregate ultra-high performance concrete and a preparation method thereof. The silica fume dispersant used in the preparation of the coarse aggregate ultra-high performance concrete of the present invention is obtained by modifying graphene oxide, and the obtained silica fume dispersant can effectively disperse silica fume, and the synergistic effect of the silica fume dispersant and silica fume after combination improves the problem of reduced strength and durability of concrete in the later stage.

[0005] The object of the present invention is to provide a coarse aggregate ultra-high performance concrete, which comprises the following components in terms of mix ratio: cement 650-800 kg / m 3 , silica fume 200~300kg / m 3 , fly ash 100~150kg / m 3, Sand 600~750kg / m 3 , Crushed stone 450~600kg / m 3 , admixture 100~200kg / m 3 , Steel fiber 150~250kg / m 3 , water reducing agent 8~15kg / m 3 , Water 100~180kg / m 3 , silica fume dispersant 0.5~1kg / m 3 The silica fume dispersant is modified graphene oxide, and the modified graphene oxide is at least one of amino graphene oxide and quaternary ammonium salt graphene oxide.

[0006] The amino graphene oxide is obtained by the following steps:

[0007] S1. Dispersing 1 to 2 parts of graphene oxide powder in 80 to 120 parts of deionized water, and ultrasonically dispersing for 30 to 60 minutes to obtain a graphene oxide dispersion liquid;

[0008] S2. 3-aminopropyltriethoxysilane and the graphene oxide dispersion liquid obtained in S1 are stirred at 80-110° C. for 8-12 hours, the obtained solution is filtered, the filter cake is rinsed 3 times with ethanol, and then rinsed 3 times with deionized water, and dried to obtain amino graphene oxide.

[0009] The quaternary ammonium salt graphene oxide is obtained by the following steps:

[0010] S1. dispersing 1 to 2 parts of graphene oxide powder in 80 to 120 parts of anhydrous ethanol, and ultrasonically dispersing for 30 to 60 minutes to obtain a graphene oxide dispersion liquid;

[0011] S2. 3-chloropropyltriethoxysilane and the graphene oxide dispersion liquid obtained in S1 are stirred at 80-110° C. for 8-12 h, the resulting solution is filtered, the filter cake is rinsed 3 times with ethanol, and then rinsed 3 times with deionized water, and dried to obtain chloropropyl graphene oxide;

[0012] S3. Disperse triethylamine and the chloropropyl graphene oxide obtained in step S2 in acetonitrile, stir at 50-80° C. for 8-10 hours, filter the resulting solution, and dry to obtain quaternary ammonium salt graphene oxide.

[0013] The present invention provides a silica fume dispersant, which is obtained by modifying the surface of graphene oxide. The positively charged amino groups on the surface of the modified graphene oxide can be effectively adsorbed by the negatively charged silica fume on the surface, thereby playing an anchoring role. The main reason why the graphene oxide has a poor dispersion effect is that its lamellar structure is easy to accumulate. After the modified graphite oxide is adsorbed on the silica fume, on the one hand, it can prevent the accumulation of the lamellar structure, and on the other hand, it reacts with the hydroxyl groups on the surface of the silica fume to reduce its surface energy. The outer layer of graphite is a hydrophobic structure, thereby playing a role of mutual dispersion.

[0014] Among them, it should be noted that:

[0015] The graphene oxide used in the present invention has 1 to 2 layers and a lateral size of 0.1 to 10 μm.

[0016] Preferably, the graphene oxide has one layer and a lateral size of 0.5 to 10 μm.

[0017] The present invention mainly adopts two silane coupling agents to modify graphene oxide. Specifically, the mass ratio of the modified group 3-aminopropyltriethoxysilane to the graphene oxide solid contained in the graphene oxide dispersion liquid is (1:1) to (3:1); the mass ratio of the modified group 3-chloropropyltriethoxysilane to the graphene oxide solid contained in the graphene oxide dispersion liquid is (1:1) to (3:1).

[0018] There are two ways to introduce amino cations in the present invention. One is that aliphatic amine directly forms ammonium salt with acid under acidic conditions, and the other is to generate quaternary ammonium salt through triethylamine and grafted graphene oxide, wherein the mass ratio of triethylamine to grafted graphene oxide is (1:1) to (3:1).

[0019] Preferably, the silica fume dispersant is a compound of amino graphene oxide and quaternary ammonium graphene oxide, and the mass ratio of amino graphene oxide to quaternary ammonium graphene oxide is (1:4) to (1:1).

[0020] Preferably, the silica ash is one or more of fully densified silica ash, semi-densified silica ash, and original ash, and the SiO2 content in the silica ash is ≥94%, and the loss on ignition is ≤2.5%.

[0021] Preferably, the sand is river sand with a fineness modulus of 2.0 to 3.0; the crushed stone is 5 to 8 mm diabase or basalt; the steel fiber is 13 mm straight steel fiber and 20 mm end hook steel fiber; the admixture is -HDC(V)UHPC admixture.

[0022] More preferably, the crushed stone is 5-8 mm diabase; and the steel fiber is 20 mm end hook type steel fiber.

[0023] The present invention also provides a method for preparing the coarse aggregate ultra-high performance concrete, comprising the following steps:

[0024] 1) Pretreatment of silica fume: dispersing silica fume dispersant into aqueous solution, stirring for 30 to 60 minutes by a magnetic stirrer at 800 to 1000 r / min, and then dispersing by ultrasonic for 1 to 2 hours, adding the obtained silica fume dispersant solution into a cement mixer, and then adding silica fume into the cement mixer three times and stirring for 40 to 60 minutes;

[0025] 2) Add cement, fly ash, sand and crushed stone, stir for 1 to 2 minutes, then add water, stir for 2 to 5 minutes, add water reducer, continue stirring for 2 to 10 minutes, then slowly add steel fiber and continue stirring for 2 to 10 minutes, discharge, cast, cure and demould to obtain coarse aggregate ultra-high performance concrete.

[0026] Preferably, the process for adding silica fume is as follows: adding 1 / 3 of the mass of silica fume at 0 to 5 minutes; adding 1 / 3 of the mass of silica fume at 10 to 15 minutes; and adding the remaining silica fume at 20 to 25 minutes.

[0027] The cement mixer used in the present invention has a higher rotation speed and adopts a movement mode of revolution and rotation. The movement trajectory covers the entire mixing barrel, and the mixing is uniform without dead angles. The semi-densified and densified silica fume can be fully dispersed and then contacted and reacted with the silica powder dispersant.

[0028] Preferably, the cement mixer is a planetary vertical shaft mixer, and the process parameters of the cement mixer in step 1) are as follows: the stirring time in the first stage is 0 to 10 minutes, and the stirring speed is 40 to 45 r / min; the stirring time in the second stage is 10 to 40 minutes, and the stirring speed is 60 to 70 r / min; the stirring time in the third stage is 40 to 60 minutes, and the stirring speed is 50 to 60 r / min.

[0029] Preferably, the stirring speed of the cement mixer in step 2) is 35-45 r / min.

[0030] Beneficial Effects

[0031] The present invention has the following beneficial effects:

[0032] (1) The positively charged amino groups on the surface of the modified graphene oxide can be effectively adsorbed by the negatively charged silica fume on the surface, playing an anchoring role; after the modified graphite oxide is adsorbed onto the silica fume, the hydrophobic and large-volume graphene oxide on the outer layer can effectively inhibit the agglomeration between the silica fume and the silica fume, playing a role of mutual dispersion.

[0033] (2) Graphene oxide itself has a reinforcing effect on the concrete system. Graphene oxide can make the hydrated crystals in the concrete more orderly, effectively reduce the porosity and optimize the pore structure; the lamellar structure of graphene oxide can play a bridging role in the concrete matrix, effectively delaying the development of matrix cracks and enhancing the mechanical properties of the matrix.

[0034] (3) The synergistic effect of graphene oxide and silica fume: graphene oxide can promote the secondary hydration of silica fume, reduce the calcium hydroxide content in the matrix, and reduce the adverse action points in the concrete matrix; it can increase the amount of CSH gel in the system, effectively enhance the connection between concrete and aggregate, and strengthen the density of the interface transition zone, thereby improving the performance of concrete. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is the agglomeration mechanism of graphene oxide and silica fume;

[0036] Figure 2 The present invention is the preparation and dispersion mechanism of silica fume dispersant;

[0037] Figure 3 The infrared spectra of the graphene oxide, the aminosilane coupling agent and the amino graphene oxide of the present invention are shown. DETAILED DESCRIPTION

[0038] The following is a more detailed description of the specific implementation method of the present invention, the purpose of which is to explain the concept and characteristics of the present invention, and it cannot be used to limit the scope of protection of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the scope of protection of the present invention.

[0039] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0040] The raw materials used in the embodiments and comparative examples are described as follows:

[0041] Graphene oxide powder 1: Shanghai Myrel Biochemical Technology Co., Ltd., M33420; the number of layers is 1, and the lateral size is 0.5-10 μm;

[0042] Graphene oxide powder 2: Gaoxin Technology, GX-Pgo-1; the number of layers is 1, and the lateral size is 3-5 μm;

[0043] Graphene oxide powder 3: Gaoxin Technology, GX-Pgo-2; 1 layer, lateral size 20-30 μm;

[0044] 3-Aminopropyltriethoxysilane: Zhongshan Dixin Chemical Co., Ltd.;

[0045] 4-Chloropropyltriethoxysilane: Zhongshan Dixin Chemical Co., Ltd.;

[0046] Cement: Portland cement, PII 52.5R, produced by Zhujiang Cement Plant;

[0047] Fly ash: Wuhan Lianhekang Biotechnology Co., Ltd.;

[0048] Sand: Qingyuan river sand, fineness modulus 2.0-3.0;

[0049] Crushed stone: Guangxi diabase, particle size 5-8mm;

[0050] Silica fume 1: original ash, SiO2 content 94%, purchased from Sichuan Ewende, 940UU;

[0051] Silica fume 2: semi-densified silica fume, SiO2 content 96%, purchased from Sichuan Ewende, 960U;

[0052] Silica fume 3: fully encrypted silica fume, SiO2 content 94%, purchased from Sichuan Ewende, 940DYN;

[0053] Steel fiber: end hook type steel fiber, SF100 / 60BP, purchased from Bolpais;

[0054] Water reducing agent: polycarboxylic acid water reducing agent, -IV, purchased from Jiangsu Subot;

[0055] Admixture: -HDC(V)UHPC admixture, purchased from Jiangsu Subote;

[0056] Water: Guangzhou tap water, in line with the requirements of the standard "Mixing Water for Concrete" (JGJ 63-2006).

[0057] Unless otherwise specified, the components and raw materials used in the preparation examples, embodiments and comparative examples of the present invention are all commercially available raw materials, and the components and raw materials used in each parallel experiment are all of the same kind.

[0058] The silica fume dispersant of the present invention is prepared by the following steps:

[0059] Silica fume dispersant 1

[0060] Dispersing 1 part of graphene oxide powder 1 in 100 parts of deionized water, and ultrasonically dispersing for 60 minutes to obtain a graphene oxide dispersion liquid;

[0061] 3 parts of 3-aminopropyltriethoxysilane and 1 part of graphene oxide dispersion liquid were stirred at 90° C. for 10 hours, the obtained solution was filtered, the filter cake was rinsed 3 times with ethanol, and then rinsed 3 times with deionized water, and dried to obtain silica fume dispersant 1.

[0062] Silica fume dispersant 2

[0063] Dispersing 1 part of graphene oxide powder 1 in 100 parts of deionized water, and ultrasonically dispersing for 60 minutes to obtain a graphene oxide dispersion liquid;

[0064] 3 parts of 3-chloropropyltriethoxysilane and 1 part of graphene oxide dispersion liquid were stirred at 90°C for 10 hours, the obtained solution was filtered, the filter cake was rinsed with ethanol 3 times, and then rinsed with deionized water 3 times, and dried to obtain chloropropyl graphene oxide;

[0065] 3 parts of triethylamine and 1 part of chloropropyl graphene oxide were dispersed in acetonitrile, stirred at 80° C. for 10 hours, and then the solvent was removed and dried to obtain silica fume dispersant 2.

[0066] like Figure 2 The infrared spectrum of the graphene oxide after the reaction shows that 3400 cm -1 The intensity of the hydroxyl peak decreased, and the peak at 1034 cm -1 The appearance of new silicon-oxygen bond peaks proves that amino-oxide graphene has been successfully synthesized.

[0067] Examples 1 to 11

[0068] A method for preparing coarse aggregate ultra-high performance concrete comprises the following steps:

[0069] Silica fume pretreatment: disperse 1 part of silica fume dispersant into 100 parts of aqueous solution, stir thoroughly for 50 minutes with a magnetic stirrer at 800-1000r / min, and then disperse by ultrasound for 2 hours. Add the obtained silica fume dispersant solution to the cement mixer, add 1 / 3 of the mass of silica fume at 0-5min; add 1 / 3 of the mass of silica fume at 10-15min; add the remaining silica fume at 20-25min. The process parameters of the cement mixer are: the first stage stirring time is 0-10min, and the stirring speed is 45r / min; the second stage stirring time is 10-40min, and the stirring speed is 65r / min; the third stage stirring time is 40-60min, and the stirring speed is 55r / min;

[0070] Cement, fly ash, sand and gravel were added and stirred for 2 minutes. Then water was added and stirred for 5 minutes. Then water reducer was added and stirred for 5 minutes. Then steel fiber was slowly added and stirred for 5 minutes. The stirring speed was 35 r / min. The material was discharged, cast, cured and demolded to obtain coarse aggregate ultra-high performance concrete. The formula is shown in Table 1.

[0071] Table 1 Coarse aggregate ultra-high performance concrete formula (Examples 1 to 11, in terms of mix ratio kg / m 3 )

[0072]

[0073]

[0074] Example 12

[0075] Compared with Example 4, the difference is that the graphene oxide powder used in silica fume dispersant 1 and silica fume dispersant 2 is graphene oxide powder 2;

[0076] Embodiment 13

[0077] Compared with Example 4, the difference is that the graphene oxide powder used in silica fume dispersant 1 and silica fume dispersant 2 is graphene oxide powder 3;

[0078] Comparative Examples 1-2

[0079] The preparation method is the same as that of Examples 1 to 11.

[0080] Comparative Examples 3 to 5

[0081] The preparation method is as follows

[0082] Cement, silica fume, fly ash, sand, crushed stone, silica fume dispersant 2 were added thereto, stirred for 2 minutes, and then water was added. After stirring for 5 minutes, a water reducer was added. After stirring for 5 minutes, steel fiber was slowly added and stirring was continued for 5 minutes. The stirring speed was 35 r / min. The material was discharged, cast, cured, and demolded to obtain coarse aggregate ultra-high performance concrete. The formula is shown in Table 2.

[0083] Comparative Examples 6 to 8

[0084] Compared with the preparation methods of Comparative Examples 3 to 5, the difference is that the silica fume dispersant is replaced by graphene oxide dispersing liquid.

[0085] Comparative Examples 9 to 11

[0086] Compared with the steps of Comparative Examples 1 to 3, the difference is that no silica fume dispersant is added.

[0087] Table 2 Coarse aggregate ultra-high performance concrete formula (Comparative Examples 1-11, in terms of mix ratio kg / m 3 )

[0088]

[0089] The coarse aggregate ultra-high performance concrete prepared in Examples 1 to 13 and Comparative Examples 1 to 11 was demolded and placed in 90°C hot water for curing for 3 days, and then placed in 20°C standard curing for 24 hours, and then the following performance tests were performed. The results are shown in Table 3.

[0090] The following is the test method of the performance parameters involved in the present invention:

[0091] (1) Expansion: measured by the method described in GB / 8076-2008;

[0092] (2) Compressive strength: The specimen size is 100 mm × 100 mm × 100 mm, and the test is carried out in accordance with the relevant provisions of GB / T50081-2019;

[0093] (3) Splitting tensile strength: The specimen size is 100 mm × 100 mm × 100 mm, and the test is carried out in accordance with the relevant provisions of GB / T 50081-2019;

[0094] (4) Flexural strength: The specimen size is 100 mm × 100 mm × 400 mm and is tested in accordance with the relevant provisions of GB / T50081-2019;

[0095] (5) Mercury injection test: The mercury injection test sample was prepared into a pure slurry specimen according to the water-cement ratio in the concrete mix ratio. After stirring, it was placed in a cubic grid with a side length of 1 cm. The curing method was the same as that of concrete. When the sample reached the specified age, it was taken out and dried and tested using a mercury injection instrument. The test results are shown in Table 4.

[0096] Table 3 Performance test results of embodiments and comparative examples

[0097]

[0098]

[0099] Table 4 Porosity test results of specimens under steam curing

[0100]

[0101] It can be seen from the data of the examples and comparative examples that the addition of the silica fume dispersant prepared by the present invention can improve the fluidity of concrete on the one hand, and effectively enhance the compressive strength, splitting tensile strength and flexural strength of concrete on the other hand. All meet the compressive strength ≥ 150MPa, flexural strength ≥ 25MPa, splitting tensile strength ≥ 11.8MPa, and meet the standards of most countries for UHPC with a minimum compressive strength greater than 150MPa.

[0102] From the data of Examples 4 and 8 to 11 in Table 3, it can be seen that the dispersing effects of the prepared silica fume dispersants are in the order of original silica fume > semi-densified silica fume > densified silica fume; the densified silica fume needs to increase the number of silica fume dispersants to improve its dispersibility; from the data of Comparative Examples 3 to 5, it can be seen that the fluidity, compressive strength and other properties of the obtained concrete are poor when stirred according to the ordinary process; from the data of Comparative Examples 6 to 11, it can be seen that the dispersing effect of the silica fume dispersant is much better than that of the control group without adding the silica fume dispersant.

[0103] From the data in Table 4, it can be seen that the addition of silica fume dispersant can reduce the proportion of macropores in steam-cured concrete and increase the proportion of small pores, which helps to improve the strength and durability of concrete; from Comparative Examples 9 to 11, it can be seen that without the addition of graphene oxide, the pore size is mainly distributed in multiple harmful pores, which has an adverse effect on its mechanical properties and durability. From Comparative Examples 6 to 8, it can be seen that the addition of graphene oxide dispersing liquid can reduce the proportion of multiple harmful pores to a certain extent, but the effect is not as good as the result of silica fume dispersant pretreatment of silica fume.

[0104] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A coarse aggregate ultra-high performance concrete, characterized in that: According to the mix ratio, the raw materials include cement 600-800kg / m 3 , silica fume 150~300kg / m 3 , fly ash 100~150kg / m 3 , Sand 600~750kg / m 3 , Crushed stone 350~600kg / m 3 , admixture 100~200kg / m 3 , Steel fiber 150~250kg / m 3 , water reducing agent 8~25kg / m 3 , Water 100~180kg / m 3 , silica fume dispersant 0.5~1kg / m 3 , the silica fume dispersant is modified graphene oxide, and the modified graphene oxide is at least one of amino graphene oxide and quaternary ammonium salt graphene oxide; The method for preparing a coarse aggregate ultra-high performance concrete comprises the following steps: 1) Pretreatment of silica fume: 1-2 parts of silica fume dispersant are dispersed into 80-120 parts of aqueous solution, and stirred for 30-60 minutes by a magnetic stirrer at 800-1000 r / min, and then dispersed by ultrasound for 1-2 hours. The obtained silica fume dispersant solution is added to a cement mixer, and then the silica fume is added thereto in three times and stirred for 40-60 minutes; 2) Add cement, fly ash, sand and crushed stone, stir for 1 to 2 minutes, then add water, stir for 2 to 5 minutes, add water reducer, continue stirring for 2 to 10 minutes, then slowly add steel fiber and continue stirring for 2 to 10 minutes, discharge, cast, cure, and demould to obtain coarse aggregate ultra-high performance concrete.

2. The coarse aggregate ultra-high performance concrete according to claim 1, characterized in that: The amino graphene oxide is obtained by the following steps: S1. dispersing 1 to 2 parts of graphene oxide powder in 80 to 120 parts of anhydrous ethanol, and ultrasonically dispersing for 30 to 60 minutes to obtain a graphene oxide dispersion liquid; S2. 3-aminopropyltriethoxysilane and the graphene oxide dispersion liquid obtained in S1 are stirred at 80-110° C. for 8-12 hours, the obtained solution is filtered, the filter cake is rinsed 3 times with ethanol, and then rinsed 3 times with deionized water, and dried to obtain amino graphene oxide.

3. The coarse aggregate ultra-high performance concrete according to claim 1, characterized in that: The quaternary ammonium salt graphene oxide is obtained by the following steps: S1. Dispersing 1 to 2 parts of graphene oxide powder in 80 to 120 parts of deionized water, and ultrasonically dispersing for 30 to 60 minutes to obtain a graphene oxide dispersion liquid; S2. 3-chloropropyltriethoxysilane and the graphene oxide dispersion liquid obtained in S1 are stirred at 80-110° C. for 8-12 h, the resulting solution is filtered, the filter cake is rinsed 3 times with ethanol, and then rinsed 3 times with deionized water, and dried to obtain chloropropyl graphene oxide; S3. Disperse triethylamine and the chloropropyl graphene oxide obtained in step S2 in acetonitrile, stir at 50-80° C. for 8-10 hours, filter the resulting solution, and dry to obtain quaternary ammonium salt graphene oxide.

4. The coarse aggregate ultra-high performance concrete according to claim 1, characterized in that: The graphene oxide has 1 to 2 layers and a lateral size of 0.1 to 10 μm.

5. The coarse aggregate ultra-high performance concrete according to claim 2, characterized in that: In step S2, the mass ratio of 3-aminopropyltriethoxysilane to the graphene oxide solid contained in the graphene oxide dispersion liquid is (1:1) to (3:1).

6. The coarse aggregate ultra-high performance concrete according to claim 3, characterized in that: In step S2, the mass ratio of 3-chloropropyltriethoxysilane to the graphene oxide solid contained in the graphene oxide dispersion liquid is (1:1) to (3:1); in step S3, the mass ratio of triethylamine to chloropropyl graphene oxide is (1:1) to (3:1).

7. The coarse aggregate ultra-high performance concrete according to claim 1, characterized in that: The silica fume dispersant is a compound of amino graphene oxide and quaternary ammonium graphene oxide, and the mass ratio of amino graphene oxide to quaternary ammonium graphene oxide is (1:4) to (1:1).

8. The coarse aggregate ultra-high performance concrete according to claim 1, characterized in that: The silica ash is one or more of fully densified silica ash, semi-densified silica ash, and original ash. The SiO2 content in the silica ash is ≥94%, and the ignition loss is ≤2.5%.

9. The method for preparing a coarse aggregate ultra-high performance concrete according to claim 1, characterized in that: The method for adding silica fume in step 1) is to add 1 / 3 of the mass of silica fume at 0-5min; add 1 / 3 of the mass of silica fume at 10-15min; and add the remaining silica fume at 20-25min. The cement mixer is a planetary vertical shaft mixer. The process parameters of the cement mixer in step 1) are as follows: the stirring time in the first stage is 0-10min, and the stirring speed is 40-45r / min; the stirring time in the second stage is 10-40min, and the stirring speed is 60-70r / min; the stirring time in the third stage is 40-60min, and the stirring speed is 50-60r / min. The stirring speed of the cement mixer in step 2) is 35-45r / min.

Citation Information

Patent Citations

  • Aminosilane-modified ecological nano cementing material and preparation method thereof

    CN105693164A

  • Coarse-aggregate-containing C250-strength-grade ultrahigh-performance fiber concrete and preparation method

    CN107285711A